2018
DOI: 10.22146/rpcpe.36211
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Family APGAR Score on Depression Rate in Type 2 Diabetes Mellitus Patients at First-Level Health Facilities

Abstract: To cite this article: Mutmainah A, Kusnanto H, Hilman O. The effect of family apgar score on depression rate in type 2 diabetes mellitus patients at firstlevel health facilities. Rev Prim Care Prac and Educ. 2018; 1(2):ABSTRACT Background: Diabetes Mellitus (DM) is a group of degenerative diseases. The prevalence of DM is increasing from year after year. The uncontrolled blood sugar level is associated with the incidence of depression in patients with type 2 diabetes mellitus (T2DM). Additionally, depression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The Cronbach's alpha of the subscale ranges between 0.63 and 0.83 [28,29]. The Cronbach's alpha of the Indonesian version is satisfactory (0.83) [30].…”
Section: Methodsmentioning
confidence: 98%
“…The Cronbach's alpha of the subscale ranges between 0.63 and 0.83 [28,29]. The Cronbach's alpha of the Indonesian version is satisfactory (0.83) [30].…”
Section: Methodsmentioning
confidence: 98%
“…Other studies have demonstrated the tool's validity and reliability to be satisfactory [37,38]. A previous study showed that the Indonesian version of this questionnaire had a Cronbach's alpha of 0.83 [39]. Questions are ranked from 0 (hardly ever) to 2 (almost always).…”
Section: Family Supportmentioning
confidence: 93%
“…Another study on people with disabilities found that family functioning (APGAR Family score) was significantly correlated with quality of life in various aspects (Susanti et al, 2022). In the case of type 2 diabetes, APGAR Family score and age had a 10.6% contribution in predicting the incidence of depression in that patient group (Mutmainah et al, 2018). Moderate/severe dysfunctional family function increases the risk of frailty 12.5 times (95% CI 2.998-38.038; p < 0.01) in farming families in Lampung (Larasati & Eiska, 2023).…”
Section: Discussionmentioning
confidence: 97%